Collapsin response mediator protein 4 isoforms (CRMP4a and CRMP4b) have opposite effects on cell proliferation, migration, and invasion in gastric cancer. Issue 1 (December 2016) - Guo, Haijian; Xia, Bing
Abstract Background Collapsin response mediator proteins (CRMPs) were originally identified in the nervous system and are involved in neuronal development. Similar to CRMP1, CRMP4 has a shorter transcript encoding a short isoform known as CRMP4a, and a longer transcript encoding a long isoform known as CRMP4b. Previous studies have shown that CRMP4a and CRMP4b exhibit opposing functions in neurite outgrowth. In the present study, we aimed to determine whether CRMP4a and CRMP4b have divergent effects in gastric cancer. Methods We first analyzed the mRNA and protein expression levels of CRMP4a and CRMP4b in surgical resected specimens, gastric cancer cell lines and normal gastric epithelial cell line GES-1 by quantitative real-time PCR. Open reading frame and CRMP4b shRNA were generated by lentivirus package and stable cells stably expressing CRMP4a open reading frame and CRMP4b shRNA were constructed. Then the roles of CRMP4a and CRMP4b in cell proliferation, cell cycle progression, apoptosis, migration, invasion, and adhesion were determined by cell proliferation assays, flow cytometry analysis, transwell migration and invasion assays, cell Adhesion Assay, and tumorigenicity assays in nude mice, respectively. Results CRMP4a expression was lower and CRMP4b expression was higher in tumor tissue samples as compared to paired non-tumor tissue samples. Additionally, CRMP4a expression was lower and CRMP4b expression was higher in gastric cancer cell lines than in the normal gastric epithelial cell line GES-1. CRMP4a overexpression and CRMP4b silencing suppressed cell proliferation in vitro and in vivo. Additionally, CRMP4a overexpression and CRMP4b silencing induced a significant G1-phase arrest and a decrease of the percentage of cells in S-phase. Furthermore, CRMP4a overexpression and CRMP4b silencing inhibited cell migration, invasion, and adhesion. However, neither CRMP4a overexpression nor CRMP4b silencing affected apoptosis. Conclusion These results indicate that CRMP4a and CRMP4b have opposite effects on cell proliferation, migration, and invasion in gastric cancer.